Examining Financial Distress In The Indonesian Coal Sector: The Role Of Cash Flow, Leverage, Liquidity, And Institutional Ownership - Naomi Valentina Lumban Gaol; Indra Kusumawardhani (UNIVED Press, 2026)
This study investigates the effects of operating cash flow, leverage, liquidity, and institutional ownership on financial distress in coal companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Financial distress is measured using the continuous form of the Altman Z-Score Model for Emerging Markets (2019 modification). The study utilizes secondary data from 29 firms selected through purposive sampling, resulting in 75 firm-year observations. Data are analyzed using multiple linear regression techniques. The partial (t-test) results indicate that operating cash flow, leverage, and liquidity have a significant effect on financial distress, while institutional ownership does not exhibit a significant influence. The simultaneous (F-test) results show a significance level of 0.000 with an F-statistic of 83.818, indicating that all independent variables jointly affect financial distress. Furthermore, the Adjusted R² value of 0.817 suggests that 81.7% of the variation in financial distress can be explained by the variables included in the model, while the remaining 18.3% is explained by other factors. These findings indicate that internal financial conditions play a dominant role in determining financial vulnerability in coal companies and support the use of continuous Z-Score measurements in capturing variations in firms’ financial conditions.